Social inequalities in utilization of a feminist telehealth abortion service in Brazil: A multilevel analysis - Larrea, Sara; Palència, Laia; Assis, Mariana Prandini; Borrell, Carme (Frontiers in Reproductive Health, 2022)
The disruption caused by the COVID-19 pandemic on health services around the world boosted interest over telehealth models of care. In Brazil, where abortion is heavily restricted, abortion seekers have long relied on international telehealth services to access abortion pills. We conducted a cross-sectional multilevel study to assess the effect of individual and contextual social factors on utilization of one such service. For the individual-level, we analyzed data from the records of abortion seekers contacting this feminist international telehealth organization during 2019 (n=25,920). Individual-level variables were age, race, education level and pregnancy length. Contextual-level units were states, for which we used data from the national Demographic Census and Household Surveys. Contextual-level variables where household income per capita, adjusted net school attendance rate, percentage of racialized women and income Gini Index. We fitted five multilevel Poisson Mixed-effects models with robust variance to estimate prevalence ratios (PR) of service utilization, which was defined as receiving abortion pills through the service. We found that only 8.2% of requesters got abortion pills through the service. Utilization was higher among women who were older, white, more educated and 5-8-weeks pregnant. Independently of this, service utilization was higher in states with higher income and education access, with lower proportions of racialized women, and located in the South, Southeast and Central-West regions. We concluded that while feminist telehealth abortion initiatives provide a life-saving service for some abortion seekers, they are not fully equipped to overcome entrenched social inequalities in their utilization, both at individual and contextual levels.